2018
DOI: 10.3389/fimmu.2018.01497
|View full text |Cite
|
Sign up to set email alerts
|

Potential Chronotherapeutic Optimization of Antimalarials in Systemic Lupus Erythematosus: Is Toll-Like Receptor 9 Expression Dependent on the Circadian Cycle in Humans?

Abstract: Toll-like receptor 9 (TLR9) belongs to the group of endosomal receptors of the innate immune system with the ability to recognize hypomethylated CpG sequences from DNA. There is scarce information about TLR9 expression and its association with the circadian cycle (CC). Different patterns of TLR9 expression are regulated by the CC in mice, with an elevated expression at Zeitgeber time 19 (1:00 a.m.); nevertheless, we still need to corroborate this in humans. In systemic lupus erythematosus (SLE), the inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 137 publications
0
8
0
Order By: Relevance
“…Early findings demonstrated that TLR9 was required for DCs to detect microbial nucleic acids during infection [ 32 ]. Later, TLR9 was found as a vital molecule for DCs to recognize and process nucleic acids molecules, which plays a pivotal function in the development of autoimmune diseases such as SLE [ 33 ] and psoriasis [ 34 ]. In this study, we found the expression of CXCR4, CCR7, CD83, 86 and IFN-α were up-regulated in RA serum-stimulated DCs and this effect was inhibited by HCQ, indicating that some substances in RA serum induced DC activation were blocked by HCQ.…”
Section: Discussionmentioning
confidence: 99%
“…Early findings demonstrated that TLR9 was required for DCs to detect microbial nucleic acids during infection [ 32 ]. Later, TLR9 was found as a vital molecule for DCs to recognize and process nucleic acids molecules, which plays a pivotal function in the development of autoimmune diseases such as SLE [ 33 ] and psoriasis [ 34 ]. In this study, we found the expression of CXCR4, CCR7, CD83, 86 and IFN-α were up-regulated in RA serum-stimulated DCs and this effect was inhibited by HCQ, indicating that some substances in RA serum induced DC activation were blocked by HCQ.…”
Section: Discussionmentioning
confidence: 99%
“…HCQ, although less toxic than CQ, still displays some well-known undesirable properties. The main concern is with regard to cardiomyopathy and heart failure, and the development of retinopathy due to HCQ affinity to melanin-containing cells, a secondary effect noticed in patients with lupus disease [78][79][80][81]. Therefore, it is recommended that the daily dose of CQ/HCQ in autoimmune patients should not exceed 5 mg/kg/d.…”
Section: Coronaviridaementioning
confidence: 99%
“…Moreover, drug chronotherapy (a form of therapy in which the administration of drugs is based on the 24 h circadian rhythm) with glucocorticosteroids and disease-modifying anti-rheumatic drugs was shown to be beneficial in RA [ 120 , 121 , 122 ]. This approach also appears promising in other diseases, such as SLE, but more studies would be desirable [ 123 ].…”
Section: Sleep Disturbances In Immune Diseasesmentioning
confidence: 99%